Retrocochlear function of the peripheral deafness gene Cacna1d - Satheesh, Somisetty Venkata; Bartsch, Dusan (Human molecular genetics, 2012)
Abstract. Hearing impairment represents the most common sensory deficit in humans. Genetic mutations contribute significantly to this disorder. Mostly, only malfunction of the ear is considered. Here, we assessed the role of the peripheral deafness gene Cacna1d, encoding the L-type channel Cav1.3, in downstream processing of acoustic information. To this end, we generated a mouse conditional Cacna1d-eGFPflex allele. Upon pairing with Egr2::Cre mice, Cav1.3 was ablated in the auditory brainstem, leaving the inner ear intact. Structural assessment of the superior olivary complex (SOC), an essential auditory brainstem center, revealed a dramatic volume reduction (43–47%) of major nuclei in young adult Egr2::Cre;Cacna1d-eGFPflex mice. This volume decline was mainly caused by a reduced cell number (decline by 46–56%). Abnormal formation of the lateral superior olive was already present at P4, demonstrating an essential perinatal role of Cav1.3 in the SOC. Measurements of auditory brainstem responses demonstrated a decreased amplitude in the auditory nerve between 50 and 75 dB stimulation in Egr2::Cre;Cacna1d-eGFPflex knockout mice and increased amplitudes in central auditory processing centers. Immunohistochemical studies linked the amplitude changes in the central auditory system to reduced expression of Kv1.2. No changes were observed for Kv1.1, KCC2, a determinant of inhibitory neurotransmission, and choline acetyltransferase, a marker of efferent olivocochlear neurons. Together, these analyses identify a crucial retrocochlear role of Cav1.3 and demonstrate that mutations in deafness genes can affect sensory cells and neurons alike. As a corollary, hearing aids have to address central auditory processing deficits as well.